Localization and electrical characteristics of a giant synapse in the spinal cord of the lamprey. - Ringham, G L (1975)
1. Physiological and morphological experiments were carried out to determine the characteristics of a giant synapse in the lamprey spinal cord. The presynaptic element is a Müller fibre, running the length of the spinal cord, and the post-synaptic element is a lateral interneurone. 2. Injection of the interneurone with fluorescent dye revealed several dendritic processes extending into the region of the Müller fibres and spreading over a longitudinal distance of about 150 mum. Electron microscopic examination of the Müller fibres confirmed that they do not send out processes to form synapses. Thus, the synapse is between the cylindrical fibre and one or more dendritic branches of the interneurone. 3. Measurements with intracellular electrodes showed the Müller fibres to have input resistances of about 1 Momega and space constants of 1-0-1-7 mm. The space constant was larger for hyperpolarizing pulses than for depolarizing pulses because of delayed recitification. The interneurones had input resistances of about 6 Momega. 4. The neurones were electrically as well as chemically coupled. When a current-passing electrode was placed in the fibre and hyperpolarizing pulses applied, the amplitude of the electrical coupling potential recorded from the interneurone was maximal at one position of the current-passing electrode and decreased as the electrode was moved away from the optimal position. The decrease in amplitude with electrode displacement indicated that the region of synaptic contact was very restricted. 5. The electrical synapse was highly rectifying, the forward resistance being about nine-times smaller than the backward resistance.